Better survival after stereotactic body radiation therapy following transarterial chemoembolization in nonresectable hepatocellular carcinoma: A propensity score matched analysis. (March 2019) - Wong, Tiffany CL.; Chiang, Chi-Leung; Lee, Ann-Shing; Lee, Victor HF.; Yeung, Cynthia SY.; Ho, Connie HM.; Cheung, Tan-To; Ng, Kelvin KC.; Chok, Siu-Ho; Chan, Albert CY.; Dai, Wing-Chiu; Wong, Frank CS.; et al.
Abstract: Background: This study compared outcomes of nonresectable hepatocellular carcinoma (HCC) who had transarterial chemoembolization (TACE) vs. stereotactic body radiation therapy (SBRT) after TACE (TACE + SBRT). Methods: This was a retrospective study of 2 centers in Hong Kong. There were 49 patients who had TACE + SBRT and 202 patients who had TACE alone. Propensity score matching was used to adjust for differences in patients' demographics and tumor characteristics between the 2 groups. The primary outcome was overall survival (OS) and secondary outcomes were progression-free survival (PFS) and treatment-related toxicity. Results: After matching, 49 patients were in the TACE + SBRT group and 98 patients in the TACE group with similar baseline characteristics. The 1-&3-year OS were better in TACE + SBRT group (67.2 vs. 43.9% and 36.5 vs. 13.3%, p = 0.003). The 1-&3-year PFS was also better in TACE + SBRT group (32.5 vs. 21.4% and 15.1 vs. 5.1%, p = 0.012). Radiological disease control was better in the TACE + SBRT group (98 vs. 56.7%). Risk of severe toxicity was uncommon in both treatment arms. TACE + SBRT was an independent good prognostic factor for OS and PFS in multivariate analysis, whereas AFP>200 ng/ml, large tumor and multiple tumors predicted worse OS. Conclusion: TACE + SBRT is safe and results in better survivals in nonresectable HCC patients.